Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

Ultrasound promoted efficient and green protocol for the expeditious synthesis of 1, 4 disubstituted 1, 2, 3-triazoles using Cu(II) doped clay as catalyst - Dar, Bashir Ahmad; Bhowmik, Amrita; Sharma, Amit; Sharma, Parduman R.; Lazar, Anish; Singh, A. P.; Sharma, Meena; Singh, Baldev (Applied Clay Science, 2013)
Cu(II) doped clay catalyst has been prepared by an easy technique from inexpensive starting materials and investigated for the one pot synthesis of 1, 4-disubstituted 1, 2, 3-triazoles via Huisgen [3 + 2] cycloaddition under ultrasonic irradiation at room temperature. The catalyst is highly active, selective, and stable and can be reused several times. The prepared catalyst has been characterized by XRD, BET-SA, H-2-TPR, SEM and XPS techniques. This transformation is fast, efficient and does not require nitrogen atmosphere or anoxic conditions and additive. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Catalyst support; Copper catalyst; Crystallization; selectivity; Sustainability